Advances in electronic marketing - Clarke, Irvine, 1961-; Flaherty, Theresa, 1968- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
"This book addresses Internet marketing and the World Wide Web, and other electronic marketing tools such as geographic information systems, database marketing, and mobile advertising"--Provided by publisher.